Later Life Marital Dissolution and Repartnership Status: A National Portrait. (30th April 2016) - Brown, Susan L; Lin, I-Fen; Hammersmith, Anna M; Wright, Matthew R
Abstract: Objectives: Our study compares two types of later life marital dissolution that occur after age 50—divorce and widowhood—and their associations with repartnership status (i.e., remarried, cohabiting, or unpartnered). Method: We used data from the Health and Retirement Study to provide a portrait of later life divorce and widowhood for women and men. Next, we tested whether marital dissolution type is related to women's and men's repartnered status, distinguishing among remarrieds, cohabitors, and unpartnereds, net of key sociodemographic indicators. Results: Divorcees are more often repartnered through either remarriage or cohabitation than are widoweds. This gap persists among women net of an array of sociodemographic factors. For men, the differential is reduced to nonsignificance with the inclusion of these factors. Discussion: Later life marital dissolution increasingly occurs through divorce rather than widowhood, and divorce is more often followed by repartnership. The results from this study suggest that gerontological research should not solely focus on widowhood but also should pay attention to divorce and repartnering during later life.